Effects of Microorganism Count and Physicochemical Properties of Tulum and Kashar Cheeses to Biogenic Amine Formation - Filiz Yıldız Akgül; Atila Yetişemiyen; Ebru Şenel; Fügen Durlu-Özkaya; Şebnem Öztekin; Ebru Şanlı (Turkish Journal of Agriculture: Food Science and Technology, 2019)
In this research, biogenic amine types and quantity of Tulum and Kashar cheeses were determined. In addition, the relationship between biogenic amines and some microbiological-chemical properties of cheese samples were investigated. The contents of tryptamine, phenylethylamine, putrecine, cadaverine, histamine, tyramine of totally 40 samples (20 of each cheese) were examined. While only one sample of Tulum cheeses had no biogenic amines, different levels of biogenic amines were determined in other samples. No significant relation was confirmed between the biogenic amine quantity and total aerobic mesophilic bacteria, lactic acid bacteria, enterococci bacteria count, but there was a correlation between some biogenic amine contents and chemical properties which are tyrosine, lactic acid, pH, protein and ripening coefficient. Biogenic amine levels determined in the cheeses found below hazard limit values according to what legal limit.